Pemenuhan Hak Konstitusional Warga Negara dalam Pemilihan Kepala Daerah Tahun 2020 oleh KPUD Kota Semarang - Fajar Prima Julian (LPPM Universitas Ekasakti Padang, 2023)
The main focus of Pilkada's implementation in this pandemic is that the protection of basic rights in the form of the fulfillment of political rights and the right to health must be placed on an equal footing rather than contradictory to each other. That is. This study aims to identify and analyze the urgent reasons for the fulfillment of basic rights in the 2020 regional leader elections in the Covid-19 pandemic. The problem approach in this study uses normative law. This approach explores theories, concepts, legal principles, and laws related to this study, with a focus on examining the application of rules or norms in positive law. The urgency of fulfilling political and health rights may have been addressed appropriately, but violations of health protocols should be monitored during the preparation and implementation of Pilkada. From the perspective of three basic legal values, only the value of legal certainty regarding the enforcement or imposition of sanctions in the event of a breach of a health protocol is not finely and clearly regulated by PKPU.